HEALTH OUTCOMES FOR IRAQI CHILDREN WITH ANEMIA (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Background: Anemia is a widespread condition affecting nearly half of all children under the age of five worldwide. Objective: This study aims to analyze and assess the health outcomes associated with anemia in Iraqi children. Patients and methods: A prospective study was conducted using clinical data collected from different hospitals in Iraq, including 87 children under the age of thirteen with anemia. The study period was from April 16th, 2022, to August 25th, 2023. This study aimed to establish goals for the outcomes of children with anemia, using patient data to compare changes in blood hemoglobin levels and red blood cell count percentages over the short and long term, according to CHr. VAS was also relied on to assess the long-term health physical and mental quality of life of paediatric anemia patients. Results: The clinical data shows that there were 20 cases of parasitic worm infection, 27 cases of malaria infection, and 17 cases of intestinal protozoa infection. This study aimed at determining the severity of anemia, which was classified as mild in 12 cases, moderate in 30 cases, and severe in 45 cases. In terms of nutrition, the study identified normal levels in 70 patients; 13 patients were overweight, and 4 cases exhibited signs of malnutrition.Additionally, 22 patients who were anemic took iron supplements. Over the two-year follow-up period, the study found a decrease in hemoglobin levels in patients. However, the data demonstrated a significant reduction in the long term. This investigation scrutinised the quality-of-life outcomes of patients, uncovering high health risk scores in relation to cognitive development, treatment burden, growth, and physical development. Conclusion: Anemia is a risk factor for physical and health growth, which leads to negative consequences on the quality of life of children in the long term.